THE SPATIAL STUDY OF HEALTH CONDITION OF SOCIETY TOWARDS INCOME GRADE IN PRAMBANAN, KLATEN REGENCY - Ayu Fatonah; Fitria Febri Setiyani; Hafiz Winardany; S Samidu; Bagas Anindra Murdiansyah; Fitri Nur Aini (Geosfera Indonesia, 2018)
Health is the most important aspect of the human being life. A good health will affect other aspects, one of which will affect the economic aspect of the income earned by individuals. The purpose of this research is to know the correlation between health condition and income of society in Prambanan Sub-district. This research uses quantitative descriptive research, with the research variables such as health data and income data. The sample in this study amounted to 2,235 respondents from 16 Villages in Prambanan Sub-district, Klaten. The Data Collection Method used in this research are interview, observation and questionnaire with the data analysis technique is quantitative descriptive analysis which is non statistical analysis with frequency table. The results show that there is not a significant correlation between health and income. Pereng Village has an average of "High" income with the population average monthly income > Rp. 1.500.000,00 of 52.04% but has health condition in the "Medium" level. Randusari Village has health condition in "Medium" level whereas Randusari Village has average "Low" income with population with average income per month < Rp. 500.000,00 for 44,44%. Keywords: Health Conditions, Income References Alviana, Hendika. 2017. The Development of the Economic Potential of the Local Areas to Reduce the Gap in Growth between Subdistrict in Sukoharjo Regency years 2010-2015. [Article Scientific Publications]. Surakarta: Muhammadiyah University Of Surakarta Atmawikarta, Arum. (2009). "A health Investment For economic development". BAPPENAS: Director of Community Health and Nutrition BPS Klaten Regency. (2016). Human development Index Klaten 2016. Klaten Regency and Klaten: BPS/BPS-Statistics of Klaten Regency. BPS Klaten Regency. (2016). Sub Prambanan in Number 2016. Klaten Regency and Klaten: BPS/BPS-Statistics of Klaten Regency. Fadhilah, Achmad. Spatial Analysis of the Level of Insecurity Dengue Feverfor Priority Handling System Using geographical InfromasiPrambanan Sub-district Klaten Regency. Analysis of the Spatial Level, 295-305. Hartono, Budiantoro. (2008). Analysis of the Imbalance of Economic Development in the Province of Central Java. [Thesis]. Semarang: University of Diponegoro Klaten Regency. (2015). Community Health Profile Klaten 2015. Head Of Department: Klaten Regency. Ismail M. (2013).The Influence of Family Income Level, Education Level of the Mother and the Mother's Employment Status for Nutritional Status in the District of Darul Makmur, Nagan Raya Regency [Thesis]. University Of Teuku Umar. Muta'ali, Lutfi. 2015. The Regional Analysis Techniques for Planning regions, Spatial, and Environment. Yogyakarta: Faculty Of Geography Gadjah Mada University, Publisher. Putra, Andi NepiErtanta. (2012). Economic Growth Imbalances between Klaten Regency in Central Java province Year 1999 – 2009 [Thesis]. Yogyakarta: Atma Jaya University of Yogyakarta Sudarlan. (2015). Economic Growth, Inequality,and Poverty in Indonesia. Journal Exists, Vol 11 (1), 3036-3213 Susilo, Abdi. (2017). Analysis of Economic Growth and Inequality of Income Distribution between the Central Java Regency [Thesis]. Surakarta: Muhammadiyah University Of Surakarta. Syamsurijal. (2008). The Influence of the Level of Health of the Revenue capita Growth Rate Against in South Sumatra. Journal of Economics and Development Policy, Vo1 6 (1), 1-9. Wisana, I Dewa Gede Karma. (January 2001). Health as an Investment. Journal of Economics and the Development of Indonesia, vol. 1 (1), 42-51. Yuhendri. (2013). Influence the Quality of Education, Health,and Investment towards Growth of West Sumatra[Article Publication]. Padang: State University of Padang Yuliartika, Febriyana Niken., Larasati, Dheya Amalia., Sehan, Septia Mahadeka Putri., Okctaviana, Angel., Alfredo, Septian Briantama., (2017). Study of the Level of Knowledge of Early Warning Systems Individual and Household in the Face of Devastating Earthquake in Wonogiri. Presented at the National Seminar on Geography UMS 2017, Surakarta, Central Java, May 22, 2017 Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License